Caracterização comportamental, bioquímica e farmacológica do modelo de estresse crônico por restrição de movimento - Mograbi, Karla De Michelis [UNIFESP] (2019)
Stress can be defined as any stimulus that represents a real or virtual threat to homeostasis. When stress becomes chronic, there is an allostatic overload with pathological consequences. The main goal of this study was to characterize behaviorally, biochemically and pharmacologically a new model of chronic stress, based on movement restraint with variable duration (2, 4 or 6 h, in an unpredictable schedule) for 3 weeks. Body weight, relative weight of the adrenal glands, plasma corticosterone, brain cytokines, synaptophysin, serotonin and dopamine levels, anxiety-like (novelty suppressed feeding, elevated plus maze and open field test) motivated (sucrose negative contrast test and forced swimming test) and social behaviors (social investigation and social interaction) were assessed after the chronic protocol. The influence of these neurotransmitters on social behavior was also evaluated through the acute administration of diazepam, haloperidol and escitalopram. Stressed animals showed lower body weight gain, higher relative weight of the adrenal gland, higher levels of hippocampal cytokines, lower hippocampal serotoin levels, higher dopamine and serotonin turnover levels in the amygdala, reduced suppression of low concentration sucrose solution and increased immobility in the forced swim test, anxiety-like behavior in social context and higher aggressiveness. Acute treatment with escitalopram improved social behavior changes. We propose the use of this model as a tool for the study of changes induced by chronic stress and possible treatments for chronic-stress induced behaviors.